Long-Term Drug-Free Remission and Visual Outcomes in Sympathetic Ophthalmia. (4th March 2017) - Payal, Abhishek R.; Foster, C. Stephen
ABSTRACT: Purpose : To assess corticosteroid- and immunosuppressive therapy (IST)-free long-term remission in the treatment of patients with sympathetic ophthalmia (SO), a vision-robbing disease that can span a lifetime. Methods : The medical records of 19 patients with SO aged 16.1 to 94.95 years (median age 58.56 years) with median follow-up of 7.10 years (mean, 6.41; range, 2.5 to 8.63 years) were retrospectively examined. Results : All patients achieved control of inflammation, 13 of them for 2 years or more. Three (15.78%) of the 19 patients maintained remission without IST and corticosteroids for more than 5 years with vision of 20/25 or better in the sympathizing eye. Thirteen patients (68.42%) were inactive on IST or corticosteroids or in combination therapy. Eleven patients (57.9%) maintained visual acuity of 20/40 or better at the end of follow-up. Conclusion : Even with a devastating and possibly lifelong disease like sympathetic ophthalmia, long-term remission off all IST and corticosteroids, and perhaps even cure, is possible.